2016
DOI: 10.3892/ol.2016.5433
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid inhibits the growth of ovarian cancer tumors by regulating p65 activity

Abstract: Abstract. Ovarian cancer patients often have poor prognosis, therefore, it is important to search for more effective therapeutic strategies to treat them. Gambogic acid (GA) exhibits an anti-tumor effect through various mechanisms, and has multiple targets in tumor cells. The present study aimed to elucidate the efficacy of GA in the treatment of ovarian cancer both in vivo and in vitro by analyzing its impact on cell survival and tumor growth through cell cycle and apoptosis analysis. GA inhibited the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…And we also found that treatment with gambogic acid significantly suppressed NF-κB and MMP-2 and MMP-9 protein expression in RA mice. Tang et al (11) suggested that gambogic acid inhibits the growth of ovarian cancer tumors through RELA/NF-κB p65 (p65) activity. Qi et al (22) indicated that gambogic acid suppressed lung metastasis of human breast carcinoma cell through protein kinase C (PKC) mediated MMP-2/9 expression inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And we also found that treatment with gambogic acid significantly suppressed NF-κB and MMP-2 and MMP-9 protein expression in RA mice. Tang et al (11) suggested that gambogic acid inhibits the growth of ovarian cancer tumors through RELA/NF-κB p65 (p65) activity. Qi et al (22) indicated that gambogic acid suppressed lung metastasis of human breast carcinoma cell through protein kinase C (PKC) mediated MMP-2/9 expression inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Gambogic acid ( Fig. 1) has anti-inflammatory, antioxidation and anticancer effects (11,12). Ma et al (13) showed that gambogic acid inhibits osteoclast formation and ovariectomy-induced osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB p65 is a well-recognized anti-apoptotic transcription factor and abnormal expression or activation of NF-κB p65 has been found in multiple types of malignant cancers such as cervical cancer, esophageal squamous cancer, ovarian cancer, breast cancer and glioma et al [13,[26][27][28][29]. NF-κB promotes tumorigenesis and therapy resistance mainly through induction of master transcription factors including signal transducer and activator of transcription 3 (STAT3) and TAZ [30].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, our data demonstrated that TKL can strongly inhibit the phosphorylation of IKKβ and IκBα, and subsequently reduce the nuclear translocation of NF-κB p65 (p65). In addition, p65 might also regulate the expression of several genes involved in apoptosis, mainly through its tight binding to the CASP9 gene, and subsequent influence on caspase-9 expression [ 37 , 38 ]. We propose that p65/caspase-9 signals may be attractive targets for treating DN, due to their pro-apoptotic activity.…”
Section: Discussionmentioning
confidence: 99%